Cartographie régionale de la susceptibilité aux laves torrentielles dans les Alpes du Sud - Mélanie Bertrand; Frédéric Liébault; Hervé Piégay (Revue de Géographie Alpine)
This article describes a regional methodology of debris-flow susceptibility mapping. The implementation of this approach is based on statistical and GIS methods and makes it possible to identify catchments in the Southern French Alps, according to their morphometric (Melton index and local slope) and sediment supply conditions (active erosion zones in headwater catchments), that are prone to debris flows because of hydrometeorological forcing. This methodology has been validated on 50 sites with very high scores; the geomorphic response was correctly predicted for 80% of the sites. The map of susceptibility to the occurrence of debris flow has been integrated into the RhyTMME project’s Web platform. This platform also offers a visualisation of the rainfall’s spatial distribution (from meteorological radar data), enabling automatic real-time detection of the triggering of debris flow at the regional scale.